Literary cynics : Borges, Beckett, Coetzee - Rose, Arthur, 1981- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"Literary Cynics reconsiders the meanings of words like cynicism and cosmopolitanism for Jorge Luis Borges, Samuel Beckett and J.M. Coetzee, testing the limits of their merely cynical cosmopolitanism. Arthur Rose takes as his starting point three moments of aesthetic crisis in the careers of these literary cynics: Borges's parables of the 1950s, Beckett's plays of the 1980s, and Coetzee's pedagogic novels of the 2000s. In their transition to a 'late style', Rose demonstrates how these writers develop rhetorical strategies for coping with fame, cosmopolitanism and aesthetic form that become useful when returning to the canonical texts of their respective 'high' periods. In addition to these 'late' works, Literary Cynics offers a rigorous rapprochement to classic, lesser known, and archival texts by the three writers, from Coetzee's Disgrace to Beckett's letters."--